Enhancing Energy Efficiency in Methanol-Based Formaldehyde Production through Heat Recovery Integration - Jon Saul Malau; Akhdan Mizbani Hasby; Ammara Naifah Adelia; Atikah Khairunnisa; Ayesha Imtiyaz Novya; Dzaki Amaanullah (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Formaldehyde is a key industrial chemical known for its high reactivity and broad applicability across sectors such as plastics, resins, textiles, and agrochemicals. Its production has evolved from early silver-catalyzed oxidation of methanol to the more efficient Formox process using iron molybdate catalysts. Despite these advancements, conventional production methods remain energy-intensive, prompting the need for sustainable alternatives. This study investigates the impact of process modification through internal heat recovery on the energy efficiency of methanol-based formaldehyde synthesis. By comparing conventional and modified process configurations, the results demonstrate that reusing reactor-generated heat to power auxiliary units significantly reduces external energy demand. The modified system achieved a 30.64% improvement in energy efficiency, underscoring the potential of heat integration strategies to enhance sustainability and reduce operational costs in formaldehyde manufacturing. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).